Faktor-Faktor yang Menyebabkan Kemiskinan di Provinsi Papua: Analisis Spatial Heterogeneity - Wahyuni, Ribut Nurul Tri; Damayanti, Arie (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
Pro-poor growth program has not been effective reducing poverty in Papua because the government does not have complete information about the spatial variation of poverty-causing factors (spatial heterogeneity). Therefore, this study will analyze poverty-causing factors using Geographically Weighted Regression (GWR) model. This study finds that the influence of the cultivated land area, use of technical irrigation, source of drinking water, and the electrical infrastructure vary spatially. In additions, multivariate K-means clustering shows that subdistricts are spatially clustered by geographical conditions. These results imply that poverty alleviation interventions should be different for different areas.